The Nursing Perspective: Emerging Competencies in Midwifery and Neonatal Care - Uvarani B. (International Journal of Women's Health Nursing And Practices, 2023)
A skilled attendant is a qualified healthcare practitioner, such as a midwife, doctor, or nurse, who has received appropriate education and training to effectively handle uncomplicated pregnancies, childbirth, and the immediate postnatal period. They are equipped to identify, manage, and refer any complications that may arise in women and newborns. Skilled attendants have the necessary knowledge and skills to manage normal pregnancies and childbirth, and their presence during delivery is crucial in reducing maternal mortality rates. The provision of maternity care by qualified professionals is associated with a decrease in maternal mortality rates. It is widely recognized that ensuring all pregnant women receive medical attention during delivery is one of the most important steps in lowering the risk of maternal mortality. Skilled care refers to the comprehensive healthcare services provided by qualified healthcare providers throughout pregnancy, delivery, and the immediate postpartum period. This includes having the necessary equipment and being supported by a well-functioning healthcare system that includes emergency obstetric care, transportation, and referral facilities. The role of skilled attendants in reducing the risk of pregnancy-related complications and improving overall maternal safety has been acknowledged by organizations such as the World Health Organization (WHO), the International Confederation of Midwives, and the International Federation of Obstetricians and Gynecologists (FIGO). These organizations have agreed to use the term “skilled attendant” to refer to healthcare workers who can offer skilled care. A qualified birth attendant, according to the international definition of a midwife, is a midwife who has completed the required education and obtained the necessary permissions to practice. Midwives play a crucial role in ensuring the highest standards of education, regulation, and supervision in their practice, aiming to provide the best possible care for women and protect vulnerable populations. They use various sources of information, intuition, critical thinking, and clinical judgment in their decision-making process. Midwifery is a dynamic and methodical process that adapts to each woman’s changing health status and predicts potential issues. Midwives also emphasize the involvement of women and their families in the decision-making process, including developing a plan of care for a healthy pregnancy, safe delivery, and adjusting to the new family dynamic.
Keywords: Midwifery; attitudes; communication; competencies; safe